Drug-resistant tuberculosis: time for visionary political leadership - Abubakar, Ibrahim; Zignol, Matteo; Falzon, Dennis; Raviglione, Mario; Ditiu, Lucica; Masham, Susan; Adetifa, Ifedayo; Ford, Nathan; Cox, Helen; Lawn, Stephen D; Marais, Ben J; McHugh, Timothy D; et al. (The Lancet infectious diseases, 2013)
Two decades ago, WHO declared tuberculosis a global emergency, and invested in the highly cost-effective directly observed treatment short-course programme to control the epidemic. At that time, most strains of Mycobacterium tuberculosis were susceptible to first-line tuberculosis drugs, and drug resistance was not a major issue. However, in 2013, tuberculosis remains a major public health concern worldwide, with prevalence of multidrug-resistant (MDR) tuberculosis rising. WHO estimates roughly 630 000 cases of MDR tuberculosis worldwide, with great variation in the frequency of MDR tuberculosis between countries. In the past 8 years, extensively drug-resistant (XDR) tuberculosis has emerged, and has been reported in 84 countries, heralding the possibility of virtually untreatable tuberculosis. Increased population movement, the continuing HIV pandemic, and the rise in MDR tuberculosis pose formidable challenges to the global control of tuberculosis. We provide an overview of the global burden of drug-resistant disease; discuss the social, health service, management, and control issues that fuel and sustain the epidemic; and suggest specific recommendations for important next steps. Visionary political leadership is needed to curb the rise of MDR and XDR tuberculosis worldwide, through sustained funding and the implementation of global and regional action plans.